Eleanor Roosevelt - Morey, Eileen, 1923- (San Diego, CA : Lucent Books, 1998)
A biography of the first wife of a president to have a public life and career of her own, devoted to helping others and working for peace.
Includes bibliographical references (p. 89-91) and index.
Keywords: Roosevelt, Eleanor, -- 1884-1962 -- Juvenile literature; Roosevelt, Eleanor, -- 1884-1962.; Presidents' spouses -- United States -- Biography -- Juvenile literature; Presidents' spouses; Women -- Biography